2017
DOI: 10.1590/s0100-83582017350100044
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Activity of Wheat and Ryegrass Plants in Competition

Abstract: -Ryegrass is an annual cycle Poacea, often considered as a weed in wheat crops. The goal of this study was to analyze oxidative stress and enzyme activity of wheat and ryegrass cultures in response to stress caused by the competition between crop and weed, in two development stages. The experiment was conducted in completely randomized design, with eight replications, in replacement series, with a population of 64 plants per pot. Treatments consisted of proportions of ryegrass and wheat plants arranged in repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Studies have demonstrated alterations in ROS production in crops as a response to weed interference, as well as changes in enzymatic activity and gene expression of antioxidant components [ 7 , 11 , 13 , 14 , 33 ]. Current research is needed to tie weed interference with crop oxidative stress more closely.…”
Section: Modulation Of Enzymes and Antioxidant Genes Induced By Wementioning
confidence: 99%
See 3 more Smart Citations
“…Studies have demonstrated alterations in ROS production in crops as a response to weed interference, as well as changes in enzymatic activity and gene expression of antioxidant components [ 7 , 11 , 13 , 14 , 33 ]. Current research is needed to tie weed interference with crop oxidative stress more closely.…”
Section: Modulation Of Enzymes and Antioxidant Genes Induced By Wementioning
confidence: 99%
“…One gap in our knowledge is the dynamic effects of weed interference on crops and changes rendered by herbicide exposure, especially at the molecular level. Antioxidant response to stress caused by weed interference and herbicide treatment in crops and weeds have been recent subjects of investigation [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Both weed interference and herbicide treatment stimulate the synthesis of antioxidant molecules in plants in response to stress [ 10 , 11 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…From the enzymatic point of view, resistant and susceptible ryegrass plants presented differentiated expression of enzymes linked to oxidative stress under intra and inter-biotypic competition. When the susceptible ryegrass was in competition with resistant ryegrass, the activities of the SOD and CAT enzymes were increased; these enzymes are produced to combat reactive oxygen species that are detrimental to plant development (Apel & Hirt, 2004;Agostinetto et al, 2017b).…”
Section: Biotypic Competitive Abilitymentioning
confidence: 99%